NILAI BUDAYA PADA SISTEM USAHATANI POLA ‘DUSUN’ SUKU KANUM DI KAMPUNG YANGGANDUR KABUPATEN MERAUKE - Puji Susanty; Yunus Musa; Rahmadanih Rahmadanih; Sitti Bulkis (Hasanuddin University, 2019)
NILAI BUDAYA PADA SISTEM USAHATANI POLA ‘DUSUN’ SUKU KANUM DI KAMPUNG YANGGANDUR KABUPATEN MERAUKE The Cultural Values on ‘Dusun’ Pattern Farming System of The “Kanum” Tribe in Yanggandur Village Merauke Regency Puji Susanty*, Yunus Musa, Rahmadanih, Sitti Bulkis *Politeknik Pertanian Yasanto, Merauke (email: pujisusanti74@gmail.com) Abstract“Dusun” is a specific area of the traditional land in Kanum Tribe, which been chosen as place for farmer to cultivated as rural areas for families or in Kanum Tribes Group Society that been inherite from generation to generation. This research aimed to describe the cultural values in managing the farming system of “dusun” pattern carried out by indigenous community of Kanum Tribe. The research was conducted in Yanggandur Village, Merauke Regency. Qualitative approach and snowball sampling method were applied to collect the data through interviews from informants. In order to analyze the data it applied data reduction techniques, presentation and conclusion as well as verification. From the research, it was indicated that the prime food crop that cultivated by Kanum Tribe in the “dusun” are ‘kumbili’. The Kanum Tribe still actively managed the farming system of “dusun” pattern because the “kumbili” farming system contained the cultural values which they had inherited from generation to generation. The cultural values contained in “kumbili” cultivation were the safety and religious value, the wisdom and mutual cooperation value, and the responsibility value.Keywords: cultural value; “dusun” pattern farming; Kanum Tribe.